2002
DOI: 10.1080/0953728021000026221
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation on workload limiting methods within ORR policies in a job shop environment

Abstract: The performances of three workload limiting policies are analysed, and the following are the three objectives: (i) assessing whether the method of workload limiting a ects the performances of Order Review and Release strategies; (ii) investigating the performances of the workload limiting methods when the mix imbalance changes; (iii) evaluating the robustness of the workload limiting methods considered. The methodological pattern followed required a simulation model of a dynamic job shop system and all the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 37 publications
1
63
0
1
Order By: Relevance
“…For example, the release method illustrated in Figure 3 is widely applied in the Workload Control literature (e.g. Wiendahl, 1992;Cigolini & Portioli-Staudacher, 2002;Philipoom & Steele, 2011;Thürer et al, 2012). Fredendall et al (2010) showed that, in job shops with a bottleneck, controlling the workload at each station outperforms bottleneck control.…”
Section: Workload Control In Shops With Bottlenecksmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the release method illustrated in Figure 3 is widely applied in the Workload Control literature (e.g. Wiendahl, 1992;Cigolini & Portioli-Staudacher, 2002;Philipoom & Steele, 2011;Thürer et al, 2012). Fredendall et al (2010) showed that, in job shops with a bottleneck, controlling the workload at each station outperforms bottleneck control.…”
Section: Workload Control In Shops With Bottlenecksmentioning
confidence: 99%
“…Cigolini & Portioli-Staudacher, 2002;Fredendall et al, 2010) or continuously at any moment in time (see, e.g. Fernandes & Carmo-Silva, 2011;Fernandes et al, 2014;Thürer et al, 2014b).…”
Section: Workload Control Release Controlling All Stations -Continuousmentioning
confidence: 99%
“…This effect, implicit in ORR systems (Melnyk and Ragatz, 1989) , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y seems very marked in the case of workload balancing systems. This also seems to be the finding of the paper by Cigolini and Portioli-Staudacher (2002), which compares a workload balancing system with several workload limiting systems.…”
Section: Workload Limiting and Workload Balancingmentioning
confidence: 63%
“…There are three main techniques for the workload control within limited workload order release system: upper bound only [15], [23]; lower bound only [11]; upper and lower bound method [17]. In [24], the authors found out that the upper bound limiting order release system performs the best.…”
Section: Limiting and Lean Based Balanced Orr Systemsmentioning
confidence: 99%